Damage detection in grinding of steel workpieces through ultrasonic waves - Alexandre, F. [UNESP]; Aguiar, P. R. [UNESP]; Götz, R. [UNESP]; Fernandez, B. O. [UNESP]; Lopes, W. N. [UNESP]; Viera, M. A.A.; Bianchi, E. C. [UNESP]; D'Addona, D. (EDP Sciences, 2018)
The quality control of the workpieces through reliable tests is of utmost importance in the manufacturing of a precision component. In this context, the monitoring of damages towards automation of the grinding process is essential for the manufacturing industry and of great interest for researchers of the area. This work proposes a technique for monitoring damages in steel parts in the grinding process, using low-cost piezoelectric diaphragms in the emitter and receiver configuration. The tests were performed in a surface grinding machine with aluminum oxide grinding wheel and SAE 4340 steel workpiece. The hardness measurements of the workpieces were carried out to identify the changes occurred from the grinding process. The signals from the transducers were sampled at a rate of 2 MHz. A spectrum analysis of the obtained signals was performed with the aim at characterizing the frequency ranges that were most related to the workpiece surface condition. The results demonstrated that the proposed method is effective to detect surface damage in steel parts in the grinding process.